Alcohol and student performance: Estimating the effect of legal access - Jason M. Lindo; Isaac D. Swensen; Glen R. Waddell (Institute for the Study of Labor (IZA), 2011)
We consider the effect of legal access to alcohol, which is known to increase drinking behavior, on academic performance. We first estimate the effect using an RD design but argue that this approach is not well-suited to the research question in our setting. Our preferred approach instead exploits the longitudinal nature of the data, essentially identifying the effect by comparing a student's academic performance before and after turning 21. We find that students' grades fall below their expected levels upon being able to drink legally, but by less than previously documented. We also show that there are effects on women and that the effects are persistent. The main results are robust to the inclusion of individual fixed effects, individual trends, and individual quadratics, in addition to other controls, that account for the expected evolution of performance as students make progress towards their degrees.
urn:nbn:de:101:1-201104113983
Keywords: I21; I18; K32; 330; alcohol; post-secondary education; minimum legal drinking age; Studierende; Jugendschutz; Alkoholkonsum; Wirkungsanalyse; Bildungsniveau; Schätzung; USA